Polish Modernism’s Essentialist Claim The Hansens and Open Form Architecture - Alexander Bala (Architektúra & Urbanizmus)
This paper traces the continuities between the post-war Polish husband-and-wife architect duo of Oskar and Zofia Hansen, and their predecessors from the interwar avant-garde, the husband-and-wife artist duo of painter Władysław Strzemiński and sculptor Katarzyna Kobro. It argues that the Hansens’ Open Form (1958) approach extended the essentialism of Strzemiński and Kobro’s theory of Unism (1924) to advance a modern architecture. This paper analyzes the design for a memorial at Auschwitz-Birkenau that the Hansens worked on as part of a team for an international competition, called the Road (1958), as the crystallization of Unism’s influence on the theory of the Open Form.